ANALISIS PERAN MEDIA DALAM UPAYA PENCEGAHAN PENYEBARAN VIRUS CORONA (COVID-19) DI INDONESIA - Dwi Putri Robiatul Adawiyah; Nurhaya Kadir (Mediakita, 2020)
The media has a very an important role in the lives of Indonesian. Some of news as a public comsumption, including corona virus. The information is necessary for in- dept analysis related how the role of media for people on the issue of the virus corona. This research uses a mixed method, by distributing Google forms and by phone interviews to people who live in 6 provinces which have a total of 50 cases exposed to the corona virus in Indonesia, including DKI Jakarta, East Java, Central Java, West Java, Banten and South Sulawesi. The results showed that the media has a major influence on people's lives, as especially internet media which is the most widely used media for people to find information about the corona virus and educate citizen about physical distancing and provide solutions to prevent corona virus. Both female and male participants in 6 provinces have the same opinion about the important role of the media in campaigning for physical distancing as an effort to prevent transmission of the corona virus. Keywords: , , .